Longitudinal evaluation of laboratory results and method precision in worldwide erythropoietin external quality assessments - Toll, Luisa; Weiss, Nathalie; Vierbaum, Laura; Schellenberg, Ingo; Thevis, Mario; Wenzel, Folker (Frontiers in Molecular Biosciences, 2024)
This study presents a longitudinal analysis of external quality assessment (EQA) results for erythropoietin (EPO) determinations conducted between 2017 and 2022 with a continuously increasing number of participating laboratories throughout the years. The aim of this work was to evaluate participant performance and methodological aspects. In each of the eleven EQA surveys, a blinded sample set of lyophilized human serum containing one sample with lower EPO concentrations (L) and one with higher EPO concentrations (H) was sent to the participating laboratories. A total of 1256 measurements were included. The median (interquartile range) fraction of participants not meeting the criteria of acceptance set at 20 % around the robust mean of the respective survey was 9.5 % (6.1 -10.7 %) (sample L) and 9.1 % (5.8 -11.8 %) (sample H) but without a clear trend in the observed period. Some surveys exhibited unusually high inter-laboratory variation, suggesting interfering components in the EQA samples. Different immunological methods and reagent manufacturers also showed variability in measurement outcomes to some extent. These findings highlight the need for continuous quality assessment in EPO measurements to ensure patient safety and allow identifying areas for further research and investigation. measurement procedures used (Favaloro et al., 2018). External 87 quality assessment (EQA) is frequently used to independently 88 evaluate and compare laboratory performance. 89 hat gelöscht: already 90 hat gelöscht: 6 91 hat gelöscht: independent 92 hat gelöscht: INSTAND e.V. -a scientific medical society 93 supporting the quality assurance in medical laboratories -introduced 94 its first EQA for EPO in 2017. INSTAND is an independent 95 accredited organization performing EQA in laboratory medicine.